BMP-6 promotes type 2 immune response during enhancement of rat mandibular bone defect healing - McColl, Logan F.; Chen, Xizhao; Solga, Michael D.; Schlegel, Kailo; Haughey, Sean P.; Lobo, Peter I.; Fread, Kristen; Zunder, Eli; Cha, Ryan; Park, Stephen; Christophel, J. Jared; Cui, Quanjun; et al. (Frontiers in Immunology, 2023)
Bone morphogenetic proteins (BMPs) are used as key therapeutic agents for the treatment of difficult fractures. While their effects on osteoprogenitors are known, little is known about their effects on the immune system. We used permutations of BMP-6 (B), vascular endothelial growth factor (V), and Hedgehog signaling pathway activator smoothened agonist (S), to treat a rat mandibular defect and investigated healing outcomes at week 8, in correlation with the cellular landscape of the immune cells in the fracture callus at week 2. Maximum recruitment of immune cells to the fracture callus is known to occur at week 2. While the control, S, V, and VS groups remained as nonunions at week 8; all BMP-6 containing groups - B, BV, BS and BVS, showed near-complete to complete healing. This healing pattern was strongly associated with significantly higher ratios of CD4 T (CD45+CD3+CD4+) to putative CD8 T cells (CD45+CD3+CD4-), in groups treated with any permutation of BMP-6. Although, the numbers of putative M1 macrophages (CD45+CD3-CD11b/c+CD38high) were significantly lower in BMP-6 containing groups in comparison with S and VS groups, percentages of putative - Th1 cells or M1 macrophages (CD45+CD4+IFN-γ+) and putative – NK, NKT or cytotoxic CD8T cells (CD45+CD4-IFN-γ+) were similar in control and all treatment groups. Further interrogation revealed that the BMP-6 treatment promoted type 2 immune response by significantly increasing the numbers of CD45+CD3-CD11b/c+CD38low putative M2 macrophages, putative - Th2 cells or M2 macrophages (CD45+CD4+IL-4+) cells and putative – mast cells, eosinophils or basophils (CD45+CD4-IL-4+ cells). CD45- non-haematopoietic fractions of cells which encompass all known osteoprogenitor stem cells populations, were similar in control and treatment groups. This study uncovers previously unidentified regulatory functions of BMP-6 and shows that BMP-6 enhances fracture healing by not only acting on osteoprogenitor stem cells but also by promoting type 2 immune response.